The Phenomenon of Ego-Splitting in Husserl's Phenomenology of Pure Phantasy. Issue 48 (3rd April 2017) - Cavallaro, Marco
ABSTRACT: Husserl's phenomenology of imagination embraces a cluster of different theories and approaches regarding the multi-faced phenomenon of imaginative experience. In this paper I consider one aspect that seems to be crucial to the understanding of a particular form of imagination that Husserl names pure phantasy. I argue that the phenomenon of Ego-splitting discloses the best way to elucidate the peculiarity of pure phantasy with respect to other forms of representative acts (such as remembering) and to any simple form of act modification (such as neutrality modification). First, I unravel the phenomenological distinctions which, respectively, oppose phantasy to perception, on the one hand, and phantasy to other forms of the so-called "intuitive re-presentations". Second, I introduce the difference between presentative and representative acts, arguing that this cannot help us to single out the defining feature of phantasy experiences. The third section draws again an important distinction between pure phantasy and neutrality modification, which allows me to finally determine an internal trait of phantasy experiences, which Husserl refers to as the "Ego-splitting" ( Ichspaltung ). In this way, I hope to contribute to a refined characterization of Husserl's phenomenology of imagination.